Análise bioeconômica do seqüestro florestal de carbono e da dívida ecológica: uma aplicação ao caso do Rio Grande do Sul - Giacomelli Sobrinho, Valny (2007)
Though heavily criticized, the Kyoto Protocol has stood out as the key political tool in addressing climate change. However the only of its instruments (IET, JI, CDM) that allows industrialized and developing countries to cooperate towards mitigation of GHGs is CDM. The underlying assumption of forestry CDM is that forest plantations (afforestation/ reforestation) might help to remove carbon dioxide (the most representative GHG) emissions. This assumption takes for granted that forest plantations might compensate for the loss of natural forests. Therefore this alleged trade-off constitutes the very focus of this study. Due to high monetary price instability in brand new markets, like the carbon offset one, the analysis abstracts out money variables. Additionally, this engine helps overcome the trap set up by monetary prices as scarcity indicators. Thus, to go along with the bioeconomic analysis, a Gordon-Schaefer fishery-like model is applied to carbon forest sequestration in Rio Grande do Sul. This state is thought of bringing an interesting picture to the analysis of the claimed trade-off between natural and planted forests. This owes both to Rio Grande do Sul s unworthy deforestation rates and to its high natural-to-planted forest ratio. This land use assortment is thought of as if there were two countries or regions: a forest-rich one, where natural forests still remain, and a forest-poor one, where afforestation and/or reforestation takes place. Only physical units (MtC) are used to calculate exchange and interest rates as well as non-monetary prices. Next, a function that assigns the land use to natural and planted forests is arrived at. As such, it works as the emission removal demand. On the other hand, the emission supply function depends on the economic growth rates. The results show that, eventually, the sustainability of economic growth hinges on a region s or country s ecological situation namely, equilibrium, credit or debt. The economic and environmental advantages of each mitigation strategy CDM and natural forest conservation are crosschecked. A nearly 40-year long overshoot rate is, after all, estimated for the forest sector in Rio Grande do Sul. The estimates suggest that CDM might help relieve environmental stress only where ecological credit is reported. Where ecological debt is already on, CDM was found unable to compensate for conservation disregard.